The Relationship between Toll-like Receptors and Helicobacter pylori-Related Gastropathies: Still a Controversial Topic - Lorena Elena Meliț; Cristina Oana Mărginean; Cristian Dan Mărginean; Maria Oana Mărginean (Journal of Immunology Research)
Innate immunity represents the first barrier against bacterial invasion. Toll-like receptors (TLRs) belong to the large family of pattern recognition receptors (PRRs), and their activation leads to the induction of inflammatory cytokines, chemokines, antigen-presenting molecules, and costimulatory molecules. Recent studies have focused on identifying the association between TLRs and Helicobacter pylori- (H. pylori-) related diseases. Therefore, this minireview focuses on assessing the role of these TLRs in the development of H. pylori-related gastropathies. Both TLR2 and TLR were found to be involved in H. pylori LPS recognition, with contradictory results most likely due to both the inability to obtain pure LPS in experimental studies and the heterogeneity of the bacterial LPS. In addition, TLR2 was found to be the most extensively expressed gene among all the TLRs in gastric tumors. High levels of TLR4 were also associated with a higher risk of gastric cancer. TLR5 was initially associated with the recognition of H. pylori flagellin, but it seems that this bacterium has developed mechanisms to escape this recognition representing an important factor involved in the persistence of this infection and subsequent carcinogenesis. TLR9, the only TLR with both anti- and proinflammatory roles, was involved in the recognition of H. pylori DNA. The dichotomous role of TLR9, promoting or suppressing the infection, depends on the gastric environment. Recently, TLR7 and TLR8 were shown to recognize purified H. pylori RNA, thereby inducing proinflammatory cytokines. TLR1 and TLR10 gene polymorphisms were associated with a higher risk for gastric cancer in H. pylori-infected individuals. Different gene polymorphisms of these TLRs were found to be associated with gastric cancer depending mostly on ethnicity. Further studies are required in order to develop preventive and therapeutic strategies against H. pylori infections based on the functions of TLRs.